Inhibition of radiographic joint damage in rheumatoid arthritis patients in DAS28 remission using single- or combined with methotrexate non biological disease-modifying antirheumatic drug therapy in routine clinical practice. Issue 1 (January 2015) - Katayama, Kou; Okubo, Takanobu; Sato, Toshikazu; Ito, Hiroshi; Fukai, Richio; Baba, Hisashi
Abstract Objective. We retrospectively investigated the inhibitory effect on radiographic joint damage (RJD) for non-biological disease-modifying antirheumatic drug (non-bioDMARD) monotherapy or methotrexate (MTX) combination therapy for rheumatoid arthritis (RA) in the disease activity score with 28 joint counts with erythrocyte sedimentation rate (DAS28) remission. Methods. Eighty-four patients (55 cases of monotherapy, 29 cases of MTX-combination therapy) in DAS28 remission (DAS28 ≤ 2.6) were investigated from 538 RA patients newly registered between February 2007 and August 2010. The patients were analyzed for radiological assessments using the modified total Sharp score/year (mTSS/y). Results. The remission rates and ΔmTSS/y for each agent using monotherapy were 7.1% and 0.17 for sulfasalazine; 11.9% and 0.49 for bucillamine (BUC); and 23.9% and 2.06 for MTX. Those using combination therapy were 6.8% and 1.39 for MTX + BUC; 23.5% and −1.64 for MTX + leflunomide; and 8.0% and 0.31 for MTX + tacrolimus. The cumulative distribution in the single and combination therapy groups showed improvement of percentages in structural remission from baseline to 1-year treatment, 34.1% to 60.9% (P < 0.05) and from 0% to 56.7%(P < 0.0001), respectively. Baseline mTSS (r = 0.67, P < 0.0001), disease duration (r = 0.40, P < 0.01), swollen joint counts (r = 0.33, P < 0.05), and anti-cyclic citrullinated peptide antibody (r = 0.31, P < 0.05) were useful predictors of RJD for non-bioDMARD monotherapy, but not for combination therapy. Conclusion. Satisfactory inhibition of RJD was observed in the DAS28 remission cases of monotherapy or MTX combination therapy with a non-bioDMARD.